Lire et lier : de l'écran au livre - Gleize, Joëlle (Verbum – Analecta Neolatina, 2012)
Digital culture is often described as carrying daunting and unseen effects. However, as continuities do exist between culture of printed books and digital culture, some of those daunting effects have already been encountered in the history of print: fear of the impossible distinction between texts in literature, of the disappearance of the author, of the omnipotence of the reader. To put them in perspective is a way to moderate them.